2017
DOI: 10.1016/j.devcel.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Apical Domain Is Required and Sufficient for the First Lineage Segregation in the Mouse Embryo

Abstract: SummaryMammalian development begins with segregation of the extra-embryonic trophectoderm from the embryonic lineage in the blastocyst. While cell polarity and adhesion play key roles, the decisive cue driving this lineage segregation remains elusive. Here, to study symmetry breaking, we use a reduced system in which isolated blastomeres recapitulate the first lineage segregation. We find that in the 8-cell stage embryo, the apical domain recruits a spindle pole to ensure its differential distribution upon div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(255 citation statements)
references
References 52 publications
9
240
0
6
Order By: Relevance
“…Notably, the fixed timing of cavitation, reported by Korotkevich et al [88], suggests that the timing of TE/ICM differentiation may also start at fertilization. In our model, the timing of TE/ICM differentiation is flexible and only requires a defined time point when polarity is defined.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the fixed timing of cavitation, reported by Korotkevich et al [88], suggests that the timing of TE/ICM differentiation may also start at fertilization. In our model, the timing of TE/ICM differentiation is flexible and only requires a defined time point when polarity is defined.…”
Section: Resultsmentioning
confidence: 99%
“…During the 8 to 16 cell divisions, cells inherit varying amounts of apically localized proteins from the apical domain – the polarized outside surface forming at the 8 cell stage (Anani et al, 2014; Johnson and Ziomek, 1981; Korotkevich et al, 2017; Watanabe et al, 2014). Inside cells are apolar, while outside cells can either be apolar or polar.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that polarization is necessary and sufficient for YAP nuclear localization, CDX2 expression, and trophoblast differentiation in mice (Cockburn et al, ; Hirate et al, ; Korotkevich et al, ). Thus, we speculated that the asynchronous CDX2 expression pattern in porcine trophoblast cells may be the result of an asynchronous polarization process in the trophoblast.…”
Section: Resultsmentioning
confidence: 99%